Diversity Synthesis of Complex Pyridines Yields a Probe of a Neurotrophic Signaling Pathway - Gray, B. Lawrence (American Chemical Society, 2008)
[Image: see text] Recognizing the value of including complex pyridines in small-molecule screening collections, we developed a previously unexplored [2 + 2 + 2]-cycloaddition of silyl-tethered diynes with nitriles. The tether provides high regioselectivity, while the solvent THF allows catalytic CpCo(CO)(2) to be used without exogenous irradiation. One of the resulting bicyclic and monocyclic (desilylated) pyridines was identified as an inhibitor of neuregulin-induced neurite outgrowth (EC(50) = 0.30 µM) in a screen that probes a pathway likely to be involved in breast cancers and schizophrenia.